Analysis of social network implementation as a tool for determining the structure of crime networks - Aprianus Daniel Lekitonung (Jurnal Mantik, 2023)
Social network analysis (SNA) is a process of mapping and analyzing interactions between people in social media, including crime. SNA can be used to determine network structure and relationships between criminal network actors through the social media used. After initial investigation, this study used the hashtag "Hayat Tahrir al-Sham" and the phrase in Arabic to crawl the data. Business intelligence is a concept and method of how we can improve the quality of decision-making in a business based on data-based systems. By using SNA terms such as density, centrality, diameter, and reciprocity. Business intelligence can be built. With the combination of SNA and BI, groups affiliated with these groups can be identified. The research also identified 10 accounts that were considered to play an important role in collaborative communication, the flow of funds, and the dissemination of radical propaganda. By finding these 10 accounts, there are many investigations that can be carried out in accordance with standard operating procedures at the authorities